EVALUTION OF THE DECISION MAKING OF THE CONTROL SYSTEM DURING EMERGENCIES OF MAN-INDUCED NATURE - L. P. Pilinevich; A. V. Hancharyk (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
This work is devoted to the development of the evaluation method of the control system sustainability during the emergencies that will allow to predict the hazards and their affect scope on human and tangible assets. The account of the principal factors has been considered on the basis of the control system sustainability evaluation during the emergencies of man-induced nature. The evaluation functions have been analysed as well as the corresponding starting positions such as optimistic, pessimistic, neutral and relatively pessimistic.